Aplikasi Quality Function Deployment dalam Peningkatan Pelayanan Rawat Inap Kelas III RSUD Dr. Saiful Anwar Malang - Sugeng Santoso, Muthma'inah (Jurnal Teknik Industri, 2000)
Dr. Saiful Anwar Malang is a state hospital has done it's job and function, but in 3rd class of paviliun room, the number of patient decrease dramatically. It's concerned with quality of this hospital. To answer this problem, research was done using Quality Function Deployment (QFD). Quality Function Deployment is a tool which design some needs include customers represented as a voice of customer and including some competitions and also groups some activities that usually called affinitas graphic ang getting a benchmarking for it's competitions